Evaluation of the in vitro susceptibility of melanized fungi from carnauba (Copernicia prunifera) to fluconazole (Research, Society and Development, 2025)
Objective: To investigate the in vitro susceptibility of melanized fungal isolates from carnauba to fluconazole. Methods: Microdilution techniques were used in sterile 96-well plates, standardized by document M38-A3 from the Clinical and Laboratory Standards Institute, in order to determine the Minimum Inhibitory Concentration (MIC) of the samples. This evaluation is necessary to determine the lowest concentration capable of inhibiting the growth of the fungus, thus verifying whether the fungus is sensitive to the drug tested. 7 isolates of black fungi were evaluated, 5 coming from the trunk and 2 from carnauba leaves. They were considered sensitive to fluconazole when the MIC was ≤ 1 μg/mL. Results: Fluconazole inhibited the growth of 4 fungi tested, presenting a variable MIC in the range of 1 μg/mL to 32 μg/mL, although only one of them was sensitive with an MIC of 1 μg/mL. Conclusion: Although fluconazole inhibited the majority of tested isolates (57.14%), only one was sensitive, while the other 6 were resistant to the drug in vitro. This medication can be used in the treatment of black fungus infections in an ineffective way and not as a first-line treatment, and can be used in combination therapy with other antifungals. The importance of raising awareness among workers involved in Carnauba extraction is highlighted regarding the use of personal protective equipment, given the risk of exposure to microorganisms resistant to drugs such as fluconazole, which can worsen the treatment of melanized fungal infections.